Pot do novega katoliškega prevoda Svetega pisma (2024) med teorijo in prakso - Krašovec, Jože (Bogoslovni vestnik, 2024)
A major challenge for any annotated translation of the Bible is the problem of textual criticism of the original text in Hebrew, Aramaic and Greek. The second challenge is the two-thousand-year tradition of hermeneutics and the specific needs of contemporary general and biblical scholarship. The third major challenge is the development of the language of translation, which is increasingly rich in philological studies, literature and literary criticism. Between 1980 and 2024, we have produced two translations of the Bible. In 1996, an annotated ecumenical translation of the Bible was published, which was subtitled the “Slovene Standard Translation” (SSP). This translation was prepared partly ad verbum, partly ad sensum, because some translators consciously altered the style of the original, despite the different agreement. In the preparation of the introductions, notes, references and appendices at the end of the book, we have relied mainly on the 1977 French Ecumenical Translation of the Bible (TOB). From 2006 to 2024, we have been working very carefully on a new annotated translation with the mandate of the Slovenian Bishops’ Conference. Thus, after decades of anticipation, we have the final version of the official translation of the Bible, which will be the basis for liturgical manuals and study purposes. This translation follows the principle of an exact translation from the original on the linguistic, semantic and literary level, and adheres to the world-wide French La Bible de Jérusalem (BJ) of 2000 in terms of the basic structure of the texts and the breakdown with intermediate headings. This edition has also been followed in the compilation and editing of the introductions, notes, references and extensive appendices at the end of the book. Our new, official translation of the Bible does not, however, abolish the previous, ecumenical translation, but complements it in all essential respects. This is evident from the fact that the same scholars from the whole French-speaking world have been involved in both types of commentary. The new Slovenian translation of the Bible complements and surpasses the French edition in the range of references and the consistency of the redaction system.
Keywords: Bible; Catholic translation (2004); katoliški prevod (2004); King James Version 1611; La Bible de Jérusalem 2000; Luther’s translation 1534; Luthrov prevod 1534; prevajanje ad sensum; prevajanje ad verbum; prevodi; Septuagint; Septuaginta; Slovene Standard Version (SSP); slovenski standardni prevod (SSP); standardizacija bibličnih lastnih imen; standardization of biblical proper names; Sveto pismo; tekstna kritika; textual criticism; translation ad sensum; translation ad verbum; translations; Vulgata; Vulgate